MILD Combustion: A Technical Review Towards Open Furnace Combustion - M. M., Noor; Andrew P., Wandel; T. F., Yusaf (2012)
Moderate or Intense Low oxygen Dilution (MILD) combustion is one of the best alternative new technologies for clean and efficient combustion. MILD combustion has been proven to be a promising combustion technology for industrial applications with decreased energy consumption due to the uniformity of temperature distribution, also producing low NO and CO emissions. This article provides a review and discussion of the recent research and development in MILD. Furthermore, the problems and focuses are summarized with some suggestions and therefore presented on upgrading an application of MILD in the future. Currently MILD combustion has been applied in closed furnace. For closed furnace, the preheating supply air is no longer required since the recirculation inside the enclosed furnace will self preheats the supply air and self dilutes the oxygen in the combustion chamber. The possibility of using open furnace MILD combustion was discussed and reviewed.